The Metaphysics of Gender and the Gender Binary - Kevin Richardson (Feminist Philosophy Quarterly)
The metaphysics of gender has largely focused on examples of interpersonal, linguistically articulated misrecognition. Cases of linguistic misgendering center an interaction between two people where one person refuses to recognize the gender identity of another. In light of these cases, metaphysicians of gender have devoted substantial attention to defining gender kinds and concepts. In this paper, I consider a different set of examples. I discuss cases of structural, materially articulated violence, patterns of targeted structural violence toward trans and gender-nonconforming people. Specifically, I argue that this kind of structural violence is explained by the gender binary, a social structure that (a) dictates the descriptive expectation that there are two biologically grounded genders, male and female, and (b) divides up social roles based on whether a person is male or female. I claim that metaphysicians of gender need to give a real definition of the gender binary, and I present my own preliminary account. The methodological upshot of this paper is that the metaphysics of gender is not limited to the task of determining who is (or is not) really a member of a gender kind.